Decision making method for operational performance of Chinese commercial banks based on scenario fuzzy sets - Yingming Yang; Meilan Yang; Zhenpei Shan (Scientific Reports)
Abstract In the original fuzzy set, after optimization, we expanded it into four categories: positive, neutral, negative, and invalid, and applied them to the scenario fuzzy set. This improvement not only fills the gap in the application scope of scenario fuzzy sets in existing literature, but also provides a more comprehensive analytical framework for performance evaluation of commercial banks. Although there have been studies focusing on the classification and application of fuzzy sets, there is still a lack of in-depth exploration on the specific improvement and multidimensional evaluation of situational fuzzy sets. To this end, we propose an improved definition of scenario fuzzy sets and derive the Hamming distance. This distance provides a more comprehensive calculation method when dealing with multi-attribute decision-making problems, enabling decision-makers to more accurately evaluate the relationships between different attributes. By combining the Hamming distance measure and TOPSIS principle, we calculate the optimal value of relative closeness. By comparing the situation fuzzy set with the improved situation fuzzy set, the results show that the improved situation fuzzy set is superior to traditional methods in terms of comprehensiveness and accuracy. This study not only enhances the practical effectiveness of scene fuzzy sets, but also provides a new perspective for subsequent academic research.